RANCANG BANGUN APLIKASI MEDIA PROMOSI HIDUP SEHAT BERBASIS ANDROID (STUDI KASUS DI DINAS KESEHATAN KABUPATEN SUMBAWA) - Shinta Esabella; Fahri Hamdani; Fahmi Yuliono (Program Studi Informatika Universitas Teknologi Sumbawa, 2019)
This research aims to design and build an Android-based healthy life promotion Media application in order to be utilized by the Health Department (DIKES). The research method used is a qualitative method of descriptive analytic and the method of data collection used in this research is the method of interviews, observations, and literature studies as well as using the method of spiral as Software development methods. The Android based healthy Live promotion Media app is built using the Java programming language and MySQL database as the Database Management System (DBMS). In the application of Healthy life promotion Media based on Android will be around especially in Sumbawa district can facilitate the viewing of health information wherever and whenever in the form of digital Media.